Developing competent public hospital managers: a qualitative study from Iran. Issue 2 (8th February 2021) - Kakemam, Edris; Janati, Ali; Mohaghegh, Bahram; Gholizadeh, Masoumeh; Liang, Zhanming
Abstract : Purpose: Hospitals need highly trained and competent managers to be responsible for the strategic development, overall operation and service provision. The identification and confirmation of core management competency requirements is a fundamental first step towards developing the competent management workforce for sustainable hospital service provision. This paper reports on the finding of a recent study focusing on identifying managerial competencies required by middle and senior-level managers in the public hospitals in Iran. Design/methodology/approach: The qualitative research design included position description analysis and focus group discussions with middle and senior-level public hospital managers in Iran. When analysing the identified knowledge, skills and attitudes, the validated MCAP framework was used to guide the grouping of them into associating management competencies. Findings: The study identified 11 to 13 key tasks required by middle and senior-level managers and confirmed that the position descriptions used by current Iranian hospitals might not truly reflect the actual core responsibilities of the management positions. The study also confirmed seven core managerial competencies required to perform these tasks effectively. These core competencies included evidence-informed decision-making; operations, administration and resource management; knowledge of healthcare environment and the organisation; interpersonal, communication qualities and relationship management; leading people and organisation; enabling and managing change and professionalism. Research limitations/implications: Competencies were identified based on managers' perceptions. Views and experiences of other stakeholders were not captured. Practical implications: The seven core management competency identified in the current study provides a clear direction of competency development among senior and middle-level managers working at the Iranian public hospitals. The study also confirms that position descriptions do not reflect the actual responsibilities of current hospital managers, which are in need to urgent review. Originality/value: This is the first study that has identified the core managerial competencies required by middle and senior-level hospital managers in Iran.